2000
DOI: 10.1007/bf03179798
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein, glutathione and glutathione S-transferase increase in a colon carcinoma

Abstract: The acquisition of resistance to anticancer agents used in chemotherapy is the main cause of treatment failure in malignant disorders, provoking tumours to become resistant during treatment, although they initially respond to it. The main multidrug resistance (MDR) mechanism in tumour cells is the expression of P-gly-coprotein (P-gly), that acts as an ATP-dependent active efflux pump of chemotherapeutic agents. Furthermore, an increased detoxification of compounds mediated by high levels of glutathione (GSH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…An antioxidant therapy such as vitamin E has been previously shown to prevent CsA-induced toxicity [38, 39, 40, 41]. Moreover, a recent publication reveals that colchicine treatment upregulates P-glycoprotein expression [42], a transmembrane efflux pump, that functions as the extrusion of toxic hydrophobic xenobiotics and drugs such as the immunosuppressants (CsA and FK506) out of cells, and that this may act to protect against chronic CsA nephrotoxicity [43, 44]. Additionally, our recent study (ASN/ISN, Abstract No.…”
Section: Discussionmentioning
confidence: 99%
“…An antioxidant therapy such as vitamin E has been previously shown to prevent CsA-induced toxicity [38, 39, 40, 41]. Moreover, a recent publication reveals that colchicine treatment upregulates P-glycoprotein expression [42], a transmembrane efflux pump, that functions as the extrusion of toxic hydrophobic xenobiotics and drugs such as the immunosuppressants (CsA and FK506) out of cells, and that this may act to protect against chronic CsA nephrotoxicity [43, 44]. Additionally, our recent study (ASN/ISN, Abstract No.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro studies, especially those performed with the multidrug resistant cell lines, it has been demonstrated that colchicine increases the glutathione level and GST activity. [51][52][53] Therefore, colchicine therapy may be responsible for less aggressive course of atherogenesis in most studies on FMF. 37 In this study; LDL, ESR, and fibrinogen levels were statistically significantly higher in the patient group.…”
mentioning
confidence: 99%
“…The acquired resistance that eventually arises in patients, after an initial period of successful treatment, has been related in some cases to the presence of these enzymes. The Pi class GST enzyme, GST P1-1, is believed to be an important factor in such resistance and its over-expression has been reported in a number of different human malignancies including lung, 4 colon, 5,6 ovary, 7 testis, 8 bladder, 9 mouth, 10 kidney, 11 esophagus, 12 and stomach. 13 GST P1-1 has been proposed as a possible tumour marker for certain types of cancer (e.g.…”
Section: Introductionmentioning
confidence: 99%